Analysing the Effects of Neuro-dynamics in Carpal Tunnel Syndrome in Pain and Disability: A Randomized Control Trial - Kuliyal Aditi, Jha K Manish, Agarwal Vaibhav, Nikku Yadav (South Eastern European Journal of Public Health, 2025)
INTRODUCTION: A peripheral neuropathy, Carpal tunnel syndrome (CTS) is chronic progressive disorder that leads to pain and disability in individuals hindering their day-to-day activities. The main symptoms include pain, numbness, tingling over median nerve distribution area. It effects majority of the population with the females being more prone to the condition than men are. Risk factors include ecological, extrinsic, intrinsic and neuropathic factors. There have been various treatment approaches for the carpal tunnel syndrome, which have been discovered in the past few years, but still a proper or peculiar approach needs to be designed. METHODOLOGY: 30 subjects screened for the inclusion and exclusion criteria. Randomization of subjects in control and experimental group, implemented. No subject left the study in between. Outcome measures including NPRS, BCTSQ and EROM (Extension) were assessed pre intervention. Control group received general (home) exercises while experimental group received static opener, one ended, two ended sliders and four levels tensioners (Neurodynamics) with home (general) exercises for 5 days. Afterwards, NPRS and EROM (Extension) assessed and at 2 weeks follow up NPRS and BCTSQ were taken. RESULTS: The data acquired from 30 individuals, irrespective of side involved and data analysis carried out. The outcome measure indicated significant improvement in both the groups after intervention and at 2 weeks follow up. Overall, when both the groups were compared the implication of neurodynamics with home (general) exercises were found to be more beneficial over control group which received home (general exercises) in NPRS (p-value – 0.36**, <0.01 ) , SSS ( p-value- 0.001*, right side), FSS (0.079**) while control group remained significant in SSS ( p-value – 0.319**) at two weeks follow up. In post group intervention comparison, Elbow extension ROM implicated superiority to neurodynamics group in right side (p –value – 0.65**) over left side (p-value – 0.907**). CONCLUSION: Neurodynamics with (home) general exercises found to be more beneficial over (home) general exercises in improving pain and disability in subjects with mild to moderate CTS patient. To add, this approach reduces the chances to undergo surgery for the CTS.